Characteristics, predictors and outcomes among 99 patients hospitalised with COVID-19 in a tertiary care centre in Switzerland: an observational analysis - Claudia Gregoriano; Daniel Koch; Sebastian Haubitz; Anna Conen; Christoph A. Fux; Beat Mueller; Luca Bernasconi; Angelika Hammerer-Lercher; Michael Oberle; Susanne Burgemeister; Hartwig Reiter; Alexander Kutz; et al. (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY